O Programa Minha Casa Minha Vida no município de Piracicaba : engajamentos e interações dos principais atores imobiliários - Danelon, Leonardo (Universidade Federal de São Carlos, 2015)
This paper discusses the Federal Government Program “Minha Casa Minha Vida” and its implementation in Piracicaba from the perspective of its interaction with the social capital in the “lens” designed by Robert Putnam. In particular, it seeks to understand the actions or reactions of the major social actors resulting from the implementation of the Program, in its context, in Piracicaba. To this end, in addition to market analyzes and their trends about prices, it was identified the main elements of social capital in order to verify their relations with the applicability public policy at the local level. It was also and firstly assumed that real estate and construction companies, in Piracicaba, had a social organization tight enough to gain advantage in the market by overpricing houses or lands and raise funds or subsidies that would be allocated a priori for a program with social order, all disguised in a market logic that legitimate opportunistic actions. As it will be shown, however, the absence of social capital - as the engagement elements, civility and even problems in facing embedded cultural values - can be obstacles to the implementation of an effective policy in solving the problems related to the issue of social housing in the country. It will also be observed that the social organization of the business community, particularly in the real estate entrepreneurs in Piracicaba, do not have enough tight relationships and social organization to confirm the initial proposal that they could have some control on the market prices.
Keywords: Programas sociais; Programa Minha Casa Minha Vida - Brasil; Subsídios governamentais; Capital social; Mercado imobiliário; Piracicaba (SP); Subsidies; Social capital; Housing policy; CIENCIAS SOCIAIS APLICADAS